Obstructed inguinal hernia containing ovary with an ovarian cyst: a case report - Amir, Wajahat; Sadaf Zafarullah; Waheed, Mohammad Rehman; Anwar, Jamal; Mohammad Sohail Asghar (Journal of the Pakistan Medical Association, 2023)
A 27-year-old married woman came to the emergency room (ER) with the chief complaint of severe pain in the abdomen for 3 days, which was more pronounced in the right iliac fossa, along with the complaint of multiple episodes of vomiting for the last 6 hours. She also gave a history of swelling in the right inguinal region for last 9 months with the complaint of mild on and off pain in the swelling. On physical examination, diagnosis of obstructed inguinal hernia was made. Ultrasonography (USG) of abdomen was of no use, as it only commented on hernial defect and not on the contents of the hernial sac. An emergency surgery was planned; marsupialisation of ovarian cyst, repositioning of fallopian tube along with ovary and herniorrhaphy was performed without any difficulty. Keywords: Ovarian hernia, Inguinal Hernia, Sliding hernia, Fertility.